Glass curtain wall radiation refrigeration film and preparation process thereof
Patent Information
- Application Number
- CN202610412982.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-03-31
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2046-03-31
AI Technical Summary
[0003]然而,将辐射制冷技术直接应用于玻璃幕墙仍面临严峻挑战,首先,现有技术多关注涂层本身的光学性能(高太阳光反射率与高红外发射率),但忽视了其与玻璃基体之间长期可靠的粘附力,玻璃幕墙在风压、热胀冷缩等作用下会产生微形变,传统的物理粘贴或普通化学粘接易出现界面疲劳、开裂或脱落,导致制冷功能失效;其次,多数辐射制冷材料性能固定,无法根据季节或昼夜温差进行调节,在冬季或寒冷夜间,持续的强辐射散热可能导致室内过冷,反而增加供暖负荷,即存在“过冷”风险;再者,幕墙外表面长期暴露于复杂环境中,灰尘积聚、紫外老化、雨水侵蚀等会严重损害膜层的制冷性能与使用寿命;鉴于此,我们提出一种玻璃幕墙辐射制冷膜及其制备工艺
1、本发明通过自修复粘附层,首次在辐射制冷膜领域实现了界面损伤的自主修复,从根本上解决了幕墙应用中因应力疲劳导致的脱粘失效问题,极大延长了使用寿命;
Smart Images

Figure REF-OBJ-1774937172781-000010 
Figure REF-OBJ-1774937172781-000011
Abstract
Description
Technical Field
[0001] This invention relates to the field of glass curtain wall membrane technology, specifically to a glass curtain wall radiative cooling film and its preparation process. Background Technology
[0002] With the development of modern architecture, glass curtain walls are widely used due to their transparency and beauty. However, the high heat gain they bring leads to huge energy consumption for building cooling. Radiation cooling technology provides a zero-energy solution for building energy conservation by dissipating heat into the cold outer space through the "atmosphere window" in the form of infrared radiation. At present, a variety of radiation cooling coatings or films have been developed and applied to building exterior walls or roofs.
[0003] However, directly applying radiative cooling technology to glass curtain walls still faces significant challenges. First, existing technologies primarily focus on the optical properties of the coating itself (high solar reflectivity and high infrared emissivity), neglecting the long-term reliable adhesion between the coating and the glass substrate. Glass curtain walls undergo micro-deformation under wind pressure, thermal expansion and contraction, etc., making traditional physical bonding or ordinary chemical bonding prone to interface fatigue, cracking, or detachment, leading to cooling failure. Second, most radiative cooling materials have fixed properties and cannot be adjusted according to seasons or diurnal temperature differences. In winter or cold nights, continuous strong radiative heat dissipation may cause indoor overcooling, increasing the heating load and posing a risk of "overcooling." Furthermore, the exterior surface of the curtain wall is exposed to a complex environment for extended periods, and dust accumulation, UV aging, and rain erosion can severely damage the cooling performance and lifespan of the film. In light of these issues, we propose a radiative cooling film for glass curtain walls and its preparation process. Summary of the Invention
[0004] The purpose of this invention is to address the shortcomings mentioned in the background section by providing a glass curtain wall radiative cooling film and its preparation process.
[0005] To solve the above-mentioned technical problems, the present invention adopts the following technical solution: A radiative cooling film for glass curtain walls, the cooling film having a layered structure, comprising, from the side closest to the glass substrate outwards: The self-healing adhesion layer, which comes into direct contact with the glass, forms a high-strength, self-healing bonding interface with the glass substrate. This layer is made from a bio-based silane-modified polyurethane prepolymer containing dynamic thiocarbamate bonds. The silane coupling agent provides the ability to chemically condense with the silanol groups (-Si-OH) on the glass surface, forming a strong Si-O-Si covalent bond. The introduced dynamic thiocarbamate bonds endow the layer with self-healing properties. When the film layer develops micro-cracks or damage at the interface due to external forces, triggered by ambient heat (such as mild heat of 40-80℃ from sunlight), the thiocarbamate bonds at the damaged site undergo a reversible exchange reaction, achieving bond reconnection and restoring the interfacial adhesion. This ensures the reliability of the composite film during long-term use in curtain walls. The optimal dry film thickness for this layer is [not specified]. The thickness is 10-50 μm; too thin and the repair capacity is insufficient, too thick and it affects light transmission and increases cost. The silane coupling agent containing mercapto groups undergoes an addition reaction with the isocyanate groups of the polyurethane prepolymer to form a dynamic thiocarbamate bond (-NH-COS-). This bond can undergo a reversible exchange reaction in the range of 40-80℃, thereby achieving self-repair of interface damage. The bio-based polyurethane used in this self-healing adhesive layer has polyol components derived from renewable biomass resources (such as castor oil, lignin, or vegetable oil), which not only reduces dependence on petroleum-based raw materials and conforms to the concept of green environmental protection, but also the dynamic thiocarbamate bond introduced in the bio-based polyurethane main chain has excellent reversible exchange capacity, ensuring the full play of the self-healing function. The bio-based carbon content of this layer material is not less than 25%, which is a typical application of biomass conversion materials. A photothermal response radiation modulation layer, disposed on top of the self-healing adhesion layer, is used to passively adjust the emissivity of the infrared band according to the ambient temperature. This layer is key to achieving intelligent cooling. It is composed of vanadium dioxide nanoparticles uniformly dispersed in polydimethylsiloxane. Vanadium dioxide is a typical phase change material; its emissivity in the mid-infrared band (especially 8-13 μm) changes drastically near its phase change temperature. This invention uses tungsten (W) or magnesium (Mg) doping to modulate the emissivity of vanadium dioxide (W)... The phase transition point can be precisely adjusted from 68℃ to a range closer to the building environment temperature of 40-65℃ (e.g., 50℃). By controlling the tungsten doping amount within the range of 1-3 at.%, the phase transition temperature can be adjusted within the 40-65℃ range. When the ambient temperature is lower than the phase transition point, In its insulating state, this layer exhibits high emissivity to atmospheric window wavelengths, allowing internal heat to radiate out efficiently; when the ambient temperature is above the phase transition point... When the layer transitions to a metallic state, its emissivity decreases, thereby automatically suppressing radiative heat dissipation and preventing "overcooling". The phase transition is not an abrupt change, but rather exhibits a gradual behavior near the phase transition point. When the ambient temperature is slightly higher than the phase transition point, Entering a partially metallic state significantly reduces emissivity, thereby effectively suppressing radiative heat dissipation; Specifically, when the temperature is below the phase transition point, the emissivity of this layer in the 8-13μm band can reach above 0.85; when the temperature is above the phase transition point, the emissivity drops to below 0.6, thereby achieving adaptive adjustment of the radiation heat dissipation capacity. A gradient porous radiation layer, disposed above the photothermal response radiation control layer, is used to efficiently emit infrared radiation in the 8-13μm wavelength band. This layer is the "engine" of radiative cooling, and its main function is to maximize the emission of heat in infrared light with a wavelength of 8-13μm. This layer is composed of tightly packed monodisperse silica microspheres with a gradient particle size distribution. From the side closest to the photothermal response radiation control layer outward, the particle size of the silica microspheres is designed to be 7-8μm, 9-10μm, and 11-13μm, forming a three-layer structure. This gradient design enhances the photon localization and radiation coupling in the 8-13μm band through gradient refractive index matching and multilayer Mie scattering, thereby achieving stronger resonant enhanced emission in the target infrared band. Its radiation efficiency is significantly higher than that of a single-size or randomly distributed porous silica layer. The total thickness of this layer is 100-300μm, which maintains a certain structural strength and light transmittance while ensuring high emissivity. An environmentally friendly interface enhancement layer, disposed above the gradient porous radiation layer, provides a superhydrophobic self-cleaning surface and protects the internal functional layers. This outermost protective layer is composed of carbon quantum dots loaded in fluorosilicone resin, with the carbon quantum dots accounting for 0.1%-2% of the total mass. The fluorosilicone resin provides an extremely stable, low-surface-energy superhydrophobic surface (water contact angle greater than 150°, roll-off angle less than 10°), allowing rainwater to quickly roll off and carry away dust, achieving self-cleaning and maintaining a clean film surface and high optical performance for a long time. The added carbon quantum dots are an environmentally friendly nanomaterial with ultraviolet absorption and downconversion luminescence properties, converting some ultraviolet light into visible light. This not only slightly enhances the film's reflection of sunlight but also reduces the photoaging of the resin matrix by decreasing the direct irradiation of the resin matrix by ultraviolet photons, thereby improving the surface's weather resistance. This layer has a relatively thin dry film thickness of 5-20 μm to minimize its impact on infrared transmission.
[0006] A process for preparing a radiative cooling film for glass curtain walls includes the following steps: S1. Self-healing adhesive layer coating: Thoroughly clean and dry the glass substrate, apply the prepared self-healing adhesive layer coating liquid evenly to the substrate through slit coating, and then cure in an oven at 80-100℃ for 10-30 minutes to form a uniform self-healing adhesive layer. S2. Preparation of photothermal response radiation regulation layer: Vanadium dioxide nanoparticles are mixed with polydimethylsiloxane prepolymer and curing agent in a certain proportion. After ultrasonic dispersion (300-500W, 30-60 minutes), the mixture is uniformly coated onto the cured self-healing adhesive layer by spraying. The mixture is then cured at 60-80℃ for 1-2 hours to form a photothermal response radiation regulation layer. S3. Construction of Gradient Porous Radiation Layer: Prepare monodisperse silica microsphere suspensions of different particle sizes (solid content 5%-10%). Use a PDMS soft template with microstructure as an aid. Employ a template-assisted layer-by-layer deposition method to flatten the PDMS soft template onto the lower surface. Apply the suspension with a doctor blade. After the solvent evaporates and the microspheres self-assemble, remove the template and apply the next layer. After each layer is applied, lightly press and flatten it to ensure tight bonding and structural order between layers. Apply small-diameter, medium-diameter, and large-diameter suspensions sequentially onto the photothermal response radiation regulation layer. After each layer is applied, dry it at 50-70℃ to allow the microspheres to self-assemble into an ordered porous layer. After all three layers are deposited, carefully remove the soft template to obtain a structurally stable gradient porous layer. Among them, the polydimethylsiloxane soft template is prepared by photolithography-replication method. Its surface has a square micropore array with a period of 10μm and a depth of 8μm, which is used to guide the self-assembly of silica microspheres to form an ordered gradient porous structure. S4. Environmentally friendly interface reinforcement layer coating: Carbon quantum dots are mixed evenly with fluorosilicone resin prepolymer liquid and applied evenly to the surface of gradient porous radiation layer by roller brush or spraying method. It is cured at 120-150℃ for 0.5-1 hour to form an environmentally friendly interface reinforcement layer, and finally the glass curtain wall radiation cooling film is obtained.
[0007] Preferably, in step S1, the preparation method of the self-healing adhesive layer coating liquid is as follows: a bio-based polyurethane prepolymer with isocyanate groups at both ends, a silane coupling agent containing mercapto groups, and a catalyst dibutyltin dilaurate are dissolved in an anhydrous solvent and reacted at 50°C for 4-6 hours under nitrogen protection to form a bio-based silane-modified polyurethane prepolymer solution containing dynamic thiocarbamate bonds. The bio-based polyurethane prepolymer is prepared using bio-based polyols as raw materials. The bio-based polyols include at least one of castor oil-based polyols, lignin-based polyols, or vegetable oil-based polyols, and the bio-based carbon content is not less than 25%.
[0008] Preferably, in step S2, the vanadium dioxide nanoparticles are tungsten-doped. Nanoparticles, where x = 0.01-0.03, have a phase transition temperature adjusted to 50±5℃; ultrasonic dispersion power is 300-500W, and dispersion time is 30-60 minutes.
[0009] Preferably, in step S3, the template is a polydimethylsiloxane soft template with a regular array structure.
[0010] Preferably, in step S3, the solid content of the silica microsphere suspension is 5%-10%, and the solvent is a mixture of ethanol and water, wherein the volume percentage of ethanol is 70%-90%.
[0011] Compared with the prior art, the beneficial effects of the present invention are: 1. This invention, through a self-healing adhesive layer, achieves autonomous repair of interface damage for the first time in the field of radiation cooling film, fundamentally solving the problem of debonding failure caused by stress fatigue in curtain wall applications and greatly extending service life; 2. This invention utilizes the phase change characteristics of vanadium dioxide to enable the radiation cooling function of the radiation cooling film to be passively and automatically switched on or adjusted according to the ambient temperature, avoiding the problem of excessive cooling in winter that may be caused by traditional fixed-performance materials, and realizing intelligent energy saving all year round.
[0012] 3. This invention uses a gradient porous silica layer to optically optimize the atmospheric window band, and combines it with a superhydrophobic self-cleaning surface to maintain high reflectivity for a long time, ensuring the continuous and efficient cooling capacity of the radiation cooling film. At the same time, the selection of materials for each layer takes into account high visible light transmittance.
[0013] 4. This invention introduces biomass conversion materials into the self-healing adhesion layer, using bio-based polyurethane instead of traditional petroleum-based polyurethane. Its polyol components are derived from renewable biomass resources (such as castor oil, lignin, or vegetable oil), and the bio-based carbon content is not less than 25%. The use of bio-based polyurethane not only maintains excellent self-healing performance and interfacial adhesion strength, but also significantly reduces the carbon footprint of the membrane, realizing the high-value recycling of agricultural / forestry waste. This aligns with the development direction of green and environmentally friendly materials and the circular economy, further enhancing the environmental friendliness and sustainable development value of this invention. Detailed Implementation
[0014] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of the embodiments. Unless otherwise specified, the embodiments and features in the embodiments of this application can be combined with each other. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0015] The present invention will describe the above technical solution in detail through the following embodiments: Example 1
[0016] A process for preparing a radiative cooling film for glass curtain walls includes the following steps: 1. Preparation of self-healing adhesive layer coating solution: Under a nitrogen atmosphere, 100g of castor oil-based polyurethane prepolymer (NCO content 5.2%, bio-based carbon content 28%), 12g of γ-mercaptopropyltriethoxysilane and 0.15g of catalyst dibutyltin dilaurate were dissolved in 250ml of anhydrous tetrahydrofuran and stirred at 50℃ for 5 hours to obtain a bio-based silane-modified polyurethane prepolymer solution containing dynamic thiocarbamate bonds; In this process, the thiol group (-SH) of γ-mercaptopropyltriethoxysilane undergoes an addition reaction with the isocyanate group (-NCO) of the polyurethane prepolymer to generate a thiocarbamate bond (-NH-COS-). This bond can undergo dynamic exchange at 40-80℃, thereby achieving a self-repair function. The castor oil-based polyurethane prepolymer is prepared using renewable castor oil as raw material, with a bio-based carbon content of 28%. It belongs to biomass conversion materials, reducing dependence on petroleum-based raw materials and conforming to the concept of green environmental protection.
[0017] 2. Self-healing adhesive layer coating: Ordinary float glass (10cm×10cm) is treated with a plasma cleaner for 2 minutes. A bio-based silane-modified polyurethane prepolymer solution containing dynamic disulfide bonds is coated onto the glass using a slit coating method. The wet film thickness is controlled to be 80μm. Then, it is placed in a 95℃ oven for curing for 20 minutes to form a self-healing adhesive layer with a thickness of about 30μm.
[0018] 3. Preparation of photothermal response radiation modulation layer: Weigh 8g of tungsten-doped vanadium dioxide nanoparticles ( Add 92g of PDMS prepolymer (Dow Corning Sylgard 184 component A) and 15g of n-hexane to a mixture with a phase transition temperature of 50℃. Disperse the mixture ultrasonically at 400W for 45 minutes. Then add 9.2g of curing agent (Sylgard 184 component B), stir to remove bubbles, and apply the mixture to the self-healing layer using a spraying method. The wet film thickness is about 120μm. Cure at 70℃ for 1.5 hours to form a photothermal response radiation regulation layer with a thickness of about 50μm.
[0019] 4. Construction of a gradient porous radiation layer: Three monodisperse silica microsphere ethanol / water suspensions (V ethanol:V water = 8:2) with a solid content of 8% were prepared: C1 (particle size 7.5 μm), C2 (particle size 9.5 μm), and C3 (particle size 12 μm). Using a PDMS soft template with a square array structure, a template-assisted layer-by-layer deposition method was adopted: the PDMS soft template was flatly attached to the photothermal response radiation regulation layer, and suspension C1 was coated with a doctor blade. After the solvent evaporated and the microspheres self-assembled, it was dried at 65°C for 40 minutes. Then the template was removed, cleaned, and reattached. C2 and C3 were coated in sequence. After each coating, the layers were lightly pressed and flattened to ensure tight bonding and structural order. After all three layers were deposited, the template was carefully removed to obtain a gradient porous radiation layer with a total thickness of about 180 μm.
[0020] 5. Environmentally friendly interface reinforcement layer coating: 1.0g of carbon quantum dots (self-made, particle size 2-5nm) were modified by surface carboxylation and then ultrasonically dispersed (200 W, 30 min) in 100g of fluorosilicone resin prepolymer (solid content 50%). 5g of crosslinking agent methyltrimethoxysilane and 0.3g of catalyst were added. The mixture was evenly brushed onto the surface of the gradient porous layer using a roller brush and cured at 135℃ for 45 minutes to form a protective layer with a thickness of about 12μm, and finally the glass curtain wall radiation cooling film was obtained.
[0021] It should be noted that carbon quantum dots can be prepared using methods known in the art, such as mixing citric acid and urea at a mass ratio of 1:2, pyrolyzing at 200°C for 2 hours, and then dialysis after cooling to obtain carbon quantum dots with a particle size of 2-5 nm and a surface rich in carboxyl groups. Example 2
[0022] The only difference between this embodiment and Embodiment 1 is that in step 3 of this embodiment, magnesium-doped vanadium dioxide nanopowder is used. The phase transition temperature was 45°C), the amount added was 12g (approximately 10.7% by mass), the amount of PDMS prepolymer was 88g, and the final photothermal response layer thickness was approximately 55μm. The remaining steps and parameters were exactly the same as in Example 1. Example 3
[0023] The only difference between this embodiment and embodiment 1 is that in step 4 of this embodiment, the structure of the gradient porous layer is adjusted to adopt a two-layer structure, with the suspension being C1 (particle size 8μm) and C3 (particle size 13μm), and the total thickness is controlled to be 150μm. The remaining steps and parameters are exactly the same as in embodiment 1. Example 4
[0024] The only difference between this embodiment and Embodiment 1 is that in step 1 of this embodiment, the thickness of the self-healing adhesion layer is adjusted to increase the wet film thickness to 120 μm, and the dry film thickness after curing is about 45 μm; in step 5, the amount of carbon quantum dots added to the environmentally friendly interface reinforcement layer is increased to 2.0 g (approximately 1.96% by mass), and the thickness after curing is about 8 μm. The remaining steps and parameters are exactly the same as in Embodiment 1.
[0025] In this embodiment, the thickness of the self-healing layer was increased to 45 μm. Tests showed that it had no negative impact on the adhesion of the upper coating, and the overall visible light transmittance remained at 68%, indicating that the optical and interface performance was not affected within the thickness range.
[0026] Comparative Example 1 The only difference between this comparative example and Example 1 is that the self-healing adhesive layer is omitted in this comparative example, and steps 1 and 2 are replaced by directly coating a layer of commercial acrylic pressure-sensitive adhesive (about 30 μm thick) on the plasma-treated glass as an adhesive layer. The remaining steps and parameters are exactly the same as in Example 1.
[0027] Comparative Example 2 The only difference between this comparative example and Example 1 is that in step 3 of this comparative example, vanadium dioxide is not added to the photothermal response radiation control layer. It is composed of only 100g of PDMS prepolymer and 10g of curing agent to form a pure PDMS layer with a thickness of about 50μm. The remaining steps and parameters are exactly the same as in Example 1. The pure PDMS layer has a high infrared emissivity (about 0.95) in the 8-13μm band, but has no temperature control function.
[0028] Comparative Example 3 The only difference between this comparative example and Example 1 is that in step 4 of this comparative example, the gradient porous radiation layer uses silica microspheres of a single particle size (9.5 μm), which are constructed through a single sedimentation process, and the total thickness is controlled to be 180 μm. The gradient structure is eliminated. The remaining steps and parameters are exactly the same as in Example 1.
[0029] Comparative Example 4 The only difference between this comparative example and Example 1 is that the environmentally friendly interface reinforcement layer is omitted, step 5 is not performed, and the gradient porous radiation layer is used as the outermost layer after it is constructed. The remaining steps and parameters are exactly the same as in Example 1. Since there is no interface reinforcement layer, the self-healing adhesive layer is directly exposed to the test environment, and its high initial bonding strength is still maintained.
[0030] According to Examples 1-4 and Comparative Examples 1-4 above, cooling film samples were prepared respectively, and their performance was tested according to the following items and procedures: 1. Optical and radiation performance testing Test procedure: The infrared emissivity of the sample in the 8-13 μm band was measured using a Fourier transform infrared spectrometer equipped with an integrating sphere; the solar reflectance of the sample in the 0.3-2.5 μm band was measured using a UV-Vis-NIR spectrophotometer; and the visible light transmittance of the sample in the 380-780 nm band was measured using a spectrophotometer.
[0031] Test objective: To evaluate the core cooling capacity (high infrared emissivity, high solar reflectivity) and its impact on curtain wall lighting.
[0032] 2. Adhesion performance and self-healing efficiency test Test process: a. Initial peel strength: The samples were tested for 180° peel strength in accordance with GB / T 2790 standard.
[0033] b. Damage and Repair: Use a sharp blade to pre-make a 2cm long scratch at the interface between the sample and the glass, and place the sample in a 60℃ oven for 2 hours for heat treatment; the selected 60℃ is within the reversible exchange temperature range of the dynamic bond of the self-healing material (40-80℃) and is higher than its glass transition temperature (Tg≈35℃), which can effectively trigger repair.
[0034] c. Peel strength after repair: Perform a 180° peel strength test again and calculate the strength recovery rate (strength after repair / initial strength × 100%).
[0035] Test objective: To verify the long-term reliability and self-healing function of the self-healing adhesion layer.
[0036] 3. Thermal performance and temperature response testing Test procedure: Construct a simulated sunlight (AM 1.5G, intensity 1000 W / m²) 2 The test platform for the radiation cooling effect was used to cover the top of the adiabatic simulation chamber (representing the interior of a building) and place it in an environmental chamber with precise temperature control. The temperature of the environmental chamber was set to 25℃ (low temperature) and 55℃ (high temperature). After the system reached thermal equilibrium, the difference between the temperature inside the simulation chamber and the ambient temperature (ΔT, a negative value represents a drop in temperature) was recorded.
[0037] Test objective: To comprehensively evaluate the actual cooling effect and verify the intelligent regulation capability of the photothermal response layer to suppress overcooling at high temperatures.
[0038] 4. Environmental durability testing Test process: a. Self-cleaning performance: ISO 12103-1 A2 grade fine dust was evenly sprinkled on the sample surface. The sample was placed at a 30° angle, and deionized water was added at a fixed flow rate using a dropper to simulate rainwater washing. The amount of water required to completely clean the surface was recorded.
[0039] b. Aging resistance: The sample was placed in an ultraviolet aging test chamber (UVA-340 lamp, 60℃ blackboard temperature) and continuously irradiated for 500 hours. The change rate of surface water contact angle and infrared emissivity before and after aging was tested.
[0040] Test objective: To evaluate the self-cleaning effect of the environmentally friendly interface reinforcement layer and the performance stability of the composite film in outdoor environments.
[0041] The specific test data are shown in Tables 1 and 2 below: Table 1 Table 2 From the test data in Tables 1 and 2 above, we can see that: The visible light transmittance of Comparative Example 4 without the interface reinforcement layer (74%) is slightly higher than that of the Example, mainly due to the weak reflection of visible light on the surface of the fluorine-free silicone resin, which leads to a slight increase in transmittance. Comparative Example 2 still exhibited a strong cooling effect at high temperatures (ΔT = -8.6℃), confirming its lack of... The temperature control function further highlights the intelligent adjustment advantages of the photothermal response layer of this invention; The measured data of emissivity change before and after the phase transition are: ε≈0.93 in the low temperature state (25℃) and ε≈0.58 in the high temperature state (55℃), which meets the design goal of "high temperature radiation suppression". Examples 1-4, utilizing a self-healing adhesive layer, achieved a high-strength and self-healing bond with the glass substrate. Their initial peel strength (8.5-10.1 N / cm) was significantly higher than that of Comparative Example 1 (6.0 N / cm), which used ordinary pressure-sensitive adhesive. More importantly, in the repair test after simulated damage, the adhesion strength recovery rate of the examples all exceeded 90%, while the recovery rate of Comparative Example 1 was less than 15%. This proves that traditional physical bonding (Comparative Example 1) will irreversibly expand and fail once micro-cracks are generated. However, the dynamic thiocarbamate bond chemical system of the present invention can achieve bond reconnection under mild heat triggering, upgrading the connection between the curtain wall film and glass from a one-time "fragile tape" to a self-repairing "lifeline". This fundamentally solves the risk of debonding in long-term application and provides a core guarantee for ultra-long service life. In particular, Examples 1-4 use bio-based polyurethane to prepare self-healing adhesive layers. While maintaining excellent self-healing performance (strength recovery rate after repair is 90%-94%), it significantly reduces the dependence on petroleum-based raw materials. The bio-based carbon content is more than 25%, which is in line with the development direction of green and environmentally friendly materials.
[0042] By introducing a photothermal response radiation modulation layer, this invention endows the thin film with "intelligence." At a low temperature of 25°C, all samples exhibited a significant cooling effect of approximately -8°C. However, when the ambient temperature rose to 55°C (simulating a hot midday or a scenario requiring protection against overcooling), the cooling effect of Examples 1-4 automatically decreased to approximately -5°C, while the pure PDMS layer in Comparative Example 2 showed no cooling effect. However, the cooling capacity remained unchanged (still -8.6℃). This comparison clearly shows that the traditional fixed high emissivity material represented by Comparative Example 2 would cause "overcooling" in winter or at night, while the thin film of this invention can sense the ambient temperature and, through... The insulating-metal phase transition passively and automatically adjusts the infrared emissivity, achieving intelligent energy saving by "strong cooling when it needs to be cold and suppressing heat dissipation when it needs to be warm," thus solving the long-standing problem of "year-round operating condition adaptability" faced by radiative cooling technology.
[0043] In terms of core radiative cooling capabilities, the design of the gradient porous radiative layer demonstrates its optical optimization value. The embodiment employs a three-layer gradient structure of 7.5μm, 9.5μm, and 12μm, achieving an average infrared emissivity of 0.91-0.93 in the 8-13μm "atmospheric window" band. In contrast, Comparative Example 3, using a single-particle-size (9.5μm) structure, exhibits a significantly reduced emissivity of 0.87. This difference directly results in Comparative Example 3 achieving a measured cooling effect (-6.5℃) far lower than the embodiment (approximately -8℃). This demonstrates that a single random scattering structure has limited radiative capability for the target band. In contrast, this invention, through a carefully designed particle size gradient, achieves "resonance enhancement" and "broadband matching" for a specific infrared band, much like focusing diffused light into laser light, greatly improving the efficiency and accuracy of heat dissipation into space. The environmentally friendly interface reinforcement layer (carbon quantum dots / fluorosilicone resin) is crucial for the long-term service of the film in harsh outdoor environments. In self-cleaning tests, the embodiment with this layer only required a small amount of water (12-18 ml) to rinse away surface dust, while Comparative Example 4 (without this layer) required 50 ml of water and was not thoroughly cleaned. After accelerated aging tests, the infrared emissivity of the embodiment decreased very little (<2%), while the decrease of Comparative Example 4 was as high as 8.5%. This proves that the outermost fluorosilicone resin provides a stable, superhydrophobic physical barrier, effectively resisting moisture and dirt corrosion; the carbon quantum dots provide "chemical sun protection" by converting ultraviolet light, reducing the photoaging of the resin matrix. The combination of the two ensures that the core function of the film remains stable under long-term exposure to wind, sun, and rain. Based on the data in the table above, Example 1 is the preferred embodiment, which achieves the best balance in various performance aspects and has the best overall performance.
[0044] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the invention can be implemented in other specific forms without departing from the spirit or essential characteristics of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description. Thus, it is intended that all variations falling within the meaning and scope of equivalents of the claims be included within the present invention.
Claims
1. A radiant cooling film for glass curtain walls, characterized in that: The cooling film has a layered structure, comprising, from the side closest to the glass substrate outwards: A self-healing adhesive layer is used to form a high-strength, self-healing bonding interface with the glass substrate; A photothermal response radiation modulation layer is disposed on the self-healing adhesion layer and is used to passively adjust the emissivity of the infrared band in the photothermal response radiation modulation layer according to the ambient temperature. A gradient porous radiation layer is disposed on the photothermal response radiation modulation layer for efficiently emitting infrared radiation in the 8-13μm band; An environmentally friendly interface enhancement layer is disposed on the gradient porous radiation layer to provide a superhydrophobic self-cleaning surface and protect the internal functional layer. The self-healing adhesive layer is made of a bio-based silane-modified polyurethane prepolymer containing dynamic thiocarbamate bonds, which is cured and has a dry film thickness of 10-50 μm. The dynamic thiocarbamate bonds can undergo a reversible exchange reaction at a temperature of 40-80°C. The bio-based silane-modified polyurethane prepolymer is prepared using at least one of lignin-based polyols or vegetable oil-based polyols as raw materials, and the bio-based carbon content of the bio-based silane-modified polyurethane prepolymer is not less than 25%. The photothermal response radiation modulation layer is composed of vanadium dioxide nanoparticles uniformly dispersed in polydimethylsiloxane matrix, wherein the mass percentage of vanadium dioxide nanoparticles is 5%-20%; the phase transition temperature of vanadium dioxide is adjusted to between 40-65℃ by doping with tungsten or magnesium elements, and the dry film thickness of this layer is 30-100μm. The gradient porous radiation layer is composed of tightly packed monodisperse silica microspheres with a gradient particle size distribution. From the side closest to the photothermal response radiation control layer outwards, the particle sizes of the silica microspheres are successively 7-8 μm, 9-10 μm, and 11-13 μm, forming a three-layer gradient structure. The total thickness of the gradient porous radiation layer is 100-300 μm.
2. The radiant cooling film for glass curtain walls as described in claim 1, characterized in that: The environmentally friendly interface reinforcement layer is composed of carbon quantum dots loaded in fluorosilicone resin, wherein the mass percentage of carbon quantum dots is 0.1%-2%; the dry film thickness of this layer is 5-20μm, and its surface water contact angle is greater than 150° and roll-off angle is less than 10°.
3. A process for preparing a radiative cooling film for glass curtain walls as described in any one of claims 1-2, characterized in that, Includes the following steps: S1. Self-healing adhesive layer coating: Clean the surface of the glass substrate, apply the self-healing adhesive layer coating liquid evenly to the substrate through slit coating, and cure at 80-100℃ for 10-30 minutes to form a self-healing adhesive layer. S2. Preparation of photothermal response radiation regulation layer: Vanadium dioxide nanoparticles are mixed with polydimethylsiloxane prepolymer and curing agent in proportion, and after ultrasonic dispersion, they are uniformly coated on the cured self-healing adhesive layer by spraying method. The mixture is cured at 60-80℃ for 1-2 hours to form a photothermal response radiation regulation layer. S3. Construction of gradient porous radiation layer: Prepare monodisperse silica microsphere suspensions with different particle sizes, and use template-assisted layer-by-layer sedimentation method to sequentially coat the suspensions with different particle sizes onto the photothermal response radiation regulation layer. After each layer is coated, dry it at 50-70℃. After it is completely dry, remove the template to form a porous layer with a gradient pore structure. S4. Environmentally friendly interface reinforcement layer coating: A fluorosilicone resin solution loaded with carbon quantum dots is uniformly applied to the surface of the gradient porous radiation layer by roller brush or spraying method, and cured at 120-150℃ for 0.5-1 hour to form an environmentally friendly interface reinforcement layer, and finally the glass curtain wall radiation cooling film is obtained.
4. The preparation process of the glass curtain wall radiant cooling film as described in claim 3, characterized in that: In step S1, the preparation method of the self-healing adhesive layer coating liquid is as follows: a polyurethane prepolymer with isocyanate groups at both ends, a silane coupling agent containing mercapto groups and a catalyst dibutyltin dilaurate are dissolved in an anhydrous solvent and reacted at 50°C for 4-6 hours under nitrogen protection to form a silane-modified polyurethane prepolymer solution containing dynamic thiocarbamate bonds.
5. The preparation process of the glass curtain wall radiant cooling film as described in claim 3, characterized in that: In step S2, the vanadium dioxide nanoparticles are tungsten-doped. Nanoparticles, where x = 0.01-0.03, have a phase transition temperature adjusted to 50±5℃; ultrasonic dispersion power is 300-500W, and dispersion time is 30-60 minutes.
6. The preparation process of the glass curtain wall radiant cooling film as described in claim 3, characterized in that: In step S3, the template is a polydimethylsiloxane soft template with a regular array structure.
7. The preparation process of the glass curtain wall radiant cooling film as described in claim 3, characterized in that: In step S3, the solid content of the silica microsphere suspension is 5%-10%, and the solvent is a mixture of ethanol and water, with ethanol accounting for 70%-90% of the volume in the solvent.
Citation Information
Patent Citations
Intelligent radiation refrigeration composite film with temperature self-adaptability and heat insulation and heat preservation functions and preparation method and application of intelligent radiation refrigeration composite film
CN114506136A
Self-repairing performance reinforcing agent for bio-based waterborne polyurethane material and self-repairing performance improving process of self-repairing performance reinforcing agent
CN116790148A
Super-hydrophobic self-cleaning radiation cooling composite coating as well as preparation method and application thereof
CN119039842A
Radiation refrigeration material with adjustable emissivity and preparation method thereof
CN120137251A